Should we consider performing oral glucose tolerance tests more frequently in postmenopausal women for optimal screening of impaired glucose tolerance? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
Objective: To investigate an optimal screening protocol for impaired glucose tolerance (IGT) and type 11 or non-insulin-dependent diabetes mellitus (DM) by using fasting plasma glucose (FPG) and oral glucose tolerance test (OGTT) in postmenopausal women. Design: One hundred consecutive postmenopausal women were screened with FPG determination, and then all underwent an OGTT. Basal serum lipid and insulin levels of these women were also determined. Insulin sensitivity was determined by using the homeostasis model assessment. Receiver operating characteristic analysis was performed to determine the efficacy of these variables in detecting women with IGT and DM, and optimal cutoff values were determined. Results: FPG with a cutoff value of 98 mg/dL had the best combination of sensitivity (71%) and specificity (76%) for the detection of IGT and DM. Combined FPG and body mass index screening (with the optimal cutoff value of 26.5 kg/m(2)) improved the sensitivity to 96% but decreased the specificity to 47%. This combined screening protocol detected 94% of the women with IGT and all diabetic women. Conclusions: Given that IGT and DM are common among postmenopausal women and DM can be prevented by nonpharmacologic interventions in women with IGT, OGTT may be used more frequently among these women. Our data indicate that for optimal screening of non-insulin-dependent DM and IGT, OGTT should be considered in postmenopausal women, especially when risk factors in addition to age are present. This model may detect most of the women with IGT and almost all diabetic women.
Keywords: screening; impaired glucose tolerance; diabetes mellitus; fasting plasma glucose; DEPENDENT DIABETES-MELLITUS; NEPHROPATHY; PREVENTION; PREVALENCE; EXERCISE; NIDDM; DIET